Sex differences in non-obstructive coronary artery disease. Issue 4 (20th January 2020) - Waheed, Nida; Elias-Smale, Suzette; Malas, Waddah; Maas, Angela H; Sedlak, Tara L; Tremmel, Jennifer; Mehta, Puja K
Abstract: Ischaemic heart disease is a leading cause of morbidity and mortality in both women and men. Compared with men, symptomatic women who are suspected of having myocardial ischaemia are more likely to have no obstructive coronary artery disease (CAD) on coronary angiography. Coronary vasomotor disorders and coronary microvascular dysfunction (CMD) have been increasingly recognized as important contributors to angina and adverse outcomes in patients with no obstructive CAD. CMD from functional and structural abnormalities in the microvasculature is associated with adverse cardiac events and mortality in both sexes. Women may be particularly susceptible to vasomotor disorders and CMD due to unique factors such as inflammation, mental stress, autonomic, and neuroendocrine dysfunction, which predispose to endothelial dysfunction and CMD. CMD can be detected with coronary reactivity testing and non-invasive imaging modalities; however, it remains underdiagnosed. This review focuses on sex differences in presentation, pathophysiologic risk factors, diagnostic testing, and prognosis of CMD.